Partial or total replacement of commercial concentrate with on-farm-grown mulberry forage: effects on lamb growth and feeding costs - Alpízar Naranjo, Andrés Humberto (2017)
Replacing commercial concentrate with mulberry foliage was evaluated in a feeding trial lasting 126 days. Forty-eight weaned male Pelibuey lambs (20.6 ± 0.80 kg of BW) were randomly allocated to four groups: (1) supplementing the basal diet with mulberry at 1% (DM basis; M-1), (2) mulberry at 0.75% plus 0.1 kg concentrate fresh matter basis (M-0.75), (3) mulberry at 0.50% plus 0.2 kg concentrate (M-0.50) and (4) basal diet plus 0.3 kg concentrate (control; M-0). During the first 90 days, the basal diet was Pennisetum purpureum forage which was substituted by a mixture of guinea grass and sugarcane from 90 days. Average daily gain (ADG, g/day), dry matter intake (DMI) and feed conversion rate (FCR; DMI/ADG) were determined. The ADG was affected (P < 0.01) by the diet, with the lowest obtained in M-1 lambs (71 ± 6.4 g/day), whereas no differences among the other groups were observed (94 ± 6.4 g DM/lamb). The DMI was higher (P < 0.01) in M-0 (937 g DM/lamb) which concomitantly affected differences in FCR (11.9, 9.9, 10.5 and 9.7 kg DMI/kg BW gain for M-1, M-0.75, M-0.50 and M-0 lambs, respectively). Final BW at slaughtering and hot or cold carcass yields were coherent with growth rate findings. Biological yield (cold carcass weight/empty BW) was higher (P < 0.01) in M-0.75. Without compromising animal productivity, replacing imported concentrate with mulberry reduced the feeding cost. Optimum results were obtained with M-75 diet. Further studies must be conducted for optimizing energy/protein ratios with different ingredients while increasing DMI and lamb growth rates in this tropical genotype.